Gaze patterns reveal aesthetic distance while viewing art. Issue 1 (24th May 2022) - Marin, Manuela M.; Leder, Helmut
Abstract: For centuries, Western philosophers have argued that aesthetic experiences differ from common, everyday pleasing sensations, and further, that mental states, such as disinterested contemplation and aesthetic distance, underlie these complex experiences. We empirically tested whether basic perceptual processes of information intake reveal evidence for aesthetic distance, specifically toward visual art. We conducted two eye tracking experiments using appropriately matched visual stimuli (environmental scenes and representational paintings) with 59 participants using two different presentation durations (25 and 6 s). Linear mixed‐effects models considering individual differences showed that affective content (pleasantness and arousal), but not stimulus composition (complexity), leads to differential effects when viewing representational paintings in comparison to environmental scenes. We demonstrate that an increase in aesthetic pleasantness induced by representational paintings during a free‐viewing task leads to a slower and deeper processing mode than when viewing environmental scenes of motivational relevance, for which we observed the opposite effect. In addition, long presentation durations led to an increase in scanning behavior during visual art perception. These empirical findings inform the debate about how aesthetic experiences differ from everyday perceptual processes by showing that the notion of aesthetic distance may be better understood by examining different modes of viewing. Abstract : We empirically tested whether basic perceptual processes of information intake reveal evidence for aesthetic distance, specifically towards visual art. We demonstrate that an increase in aesthetic pleasantness induced by representational paintings during a free‐viewing task leads to a slower and deeper processing mode than when viewing environmental scenes of motivational relevance, for which we observed the opposite effect.